1977
DOI: 10.1085/jgp.70.1.81
|View full text |Cite
|
Sign up to set email alerts
|

Ouabain-insensitive salt and water movements in duck red cells. II. Norepinephrine stimulation of sodium plus potassium cotransport.

Abstract: A B S T R A C T Catecholamines induce net salt and water movements in duck redGen. Physiol. 70:59-79. Otherwise, these two systems share a great many similarities. In both cases, net water and salt movements have a marked dependence on external cation concentrations, are sensitive to furosemide and insensitive to ouabain, and allow the substitution of rubidium for external potassium. In the presence of ouabain, but the absence of external potassium (or rubidium), a furosemide-sensitive net extrusion of sodium … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
38
1

Year Published

1977
1977
1987
1987

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 82 publications
(40 citation statements)
references
References 12 publications
1
38
1
Order By: Relevance
“…The following discussion is an attempt to explain these interactions by consideration of the thermodynamic driving forces acting on the putative carrier of the cotransport pathway. In the previous paper (Schmidt and McManus, 1977b), we presented a scheme which was helpful in explaining many of the findings reported there. Since the basic emphasis of this whole investigation has been on the study of net ion and water shifts rather than unidirectional fluxes, a detailed kinetic analysis of the model cannot be generated from these results.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The following discussion is an attempt to explain these interactions by consideration of the thermodynamic driving forces acting on the putative carrier of the cotransport pathway. In the previous paper (Schmidt and McManus, 1977b), we presented a scheme which was helpful in explaining many of the findings reported there. Since the basic emphasis of this whole investigation has been on the study of net ion and water shifts rather than unidirectional fluxes, a detailed kinetic analysis of the model cannot be generated from these results.…”
Section: Discussionmentioning
confidence: 99%
“…(5), an re1 value of 3.79 (Eel ---+36.0 mV) is predicted as necessary to prevent net sodium change. The initial rcl of 4.89 (Eel = +42.8 mV) given by 20 mM [C1]o and pHo 6.55 led to a modest but measurable net loss of cell sodium (Table III) (Schmidt and McManus, 1977b). Net sodium is transported against its electrochemical gradient simply because the total forces acting on that ion favor extrusion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Detailed examination of these quantitative relationships has shown that, for a given absolute level of beta receptor occupancy, even though a greater concentration of isoproterenol is required in hypothyroidism, the stimulation ofpotassium influx by isoproterenol is identical in normal and hypothyroid cells. When [15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30] receptors are occupied by agonist in either normal or hypothyroid cells, the same maximal stimulation of potassium influx occurs. These observations suggest that the reduction in beta receptor number per se in the hypothyroid turkey erythrocyte can account for its decreased sensitivity to isoproterenol-stimulated potassium influx.…”
Section: Discussionmentioning
confidence: 99%
“…The turkey erythrocyte satisfies these criteria by having a well-defined beta-adrenergic receptor and by responding to beta-adrenergic agonists with increased adenylate cyclase activity, cyclic AMP generation, and a cyclic AMP-linked enhancement of monovalent cation transport (16,17). This latter enhancement of monovalent cation transport is resistant to ouabain and sensitive to furosemide and represents, most likely, an activation of a sodium-plus-potassium cotransport pathway (18).…”
mentioning
confidence: 96%